Pituitary incidentalomas in paediatric population: Incidence and characteristics. (6th November 2020) - Shareef, Muhammed; Nasrallah, Mona P.; AlArab, Natally; Atweh, Lamya A.; Zadeh, Catherina; Hourani, Roula
Abstract: Objective: To determine the incidence of pituitary incidentalomas in the paediatric population and among its different age subgroups as well as to identify the characteristics of these lesions. Additionally, we aim to give a perspective on the management and follow‐up of these patients. Design and Patients: We retrospectively studied MRI of children aged 18 years or below who underwent MRI with sellar region within their field of view between January 2010 and December 2018. Measurements: Pituitary lesions were considered incidental according to the definition by the Endocrine Society. We reported the size, location and signal characteristics of each lesion. Medical charts of the subjects were reviewed for age, sex, the MRI indication and the hormonal assays levels. Results: We identified 40 pituitary lesions of which 31 were incidental lesions. The incidence of pituitary incidentaloma in our cohort was 22 per 1000 patients with female predisposition ( 64.5%) and a mean age of 11 ± 6 years. Rathke's cleft cyst was the most prevalent lesion, accounting for 67.7% followed by cystic pituitary lesions and microadenomas. The most common indications for imaging were growth disturbance (12.9%) followed by headache (9.7%). Abnormal laboratory workup was present in 13% of the subjects. Incidental lesions were more common in the older age groups compared to young children. Conclusion: Incidental pituitary lesions in the paediatric population are relatively infrequent and increases with age. Rathke's cleft cyst is the most common incidentally encountered pituitary lesion followed by cystic pituitary lesions and microadenomas.